Collaborative extended home-visits as a key to facilitating early support within the frame of a family centre in Sweden - Marie Golsäter; Ann-Christine Andersson (BMC Health Services Research)
Abstract Background All children should have the possibility to be healthy during childhood, according to the Convention on the Rights of the Child. In Sweden, the Child Health Services (CHS) support all parents and children from birth until the age of six to promote children’s health and development. Some Swedish regions have introduced an extended home-visit programme, with CHS nurses and social workers visiting first-time parents together to provide parental support in collaboration. The programme aims to expand the task of promoting the child’s health and increase the possibilities of discovering risk factors in families earlier. The aim of the present study is to describe the professionals’ experiences of collaboration when introducing the extended home-visit programme to a broader population within the frame of a family centre. Methods The study used a reflexive thematic qualitative approach with focus group interviews. All staff at the family centre were invited to participate: CHS nurses, social workers, and managers who worked with the extended home-visit programme. Data were collected through focus group interviews with each profession separately and analysed through reflexive thematic analysis. Results One overarching theme emerged: A key to facilitating early support. Three connected themes – Ease for everyone on the family’s terms, From working alone to becoming a team, and A matter of supporting structures – illuminated the participants’ experiences. Their driving force was early detection of risk factors or needs in the family, to be able to provide support. The collaboration was enhanced by the different professional competencies complementing each other. That all were located at the family centre together was also important to facilitate collaboration. Conclusions The extended home-visits were appreciated and experienced as useful by all participants. That a family centre organization already existed was one of the facilitators, functioning as a meeting point to expand the collaboration. The managers’ support was essential, and it was experienced as positive that the organization invested resources to allow employees to participate in the development of the extended home-visit programmes. This way of working has the potential to add value for the children and families, and the CHS would benefit from using the extended home-visit programme further.